Perceptual category mapping between English and Korean obstruents in non-CV positions: Prosodic location effects in second language identification skills - Park, Hanyong; de Jong, Kenneth J. (Journal of phonetics, 2017)
•We examine perceptual category mapping between Korean and English in non-CV positions.•Korean learners of English identify English consonants in intervocalic and coda contexts, with both Korean and English labels.•Mapping patterns are specific to prosodic location, indicating learning of allophones.•Due to coda neutralization in L1, English sounds in codas are “new” to the learners. This study examines the degree to which mapping patterns between native language (L1) and second language (L2) categories for one prosodic context will generalize to other prosodic contexts, and how position-specific neutralization in the L1 influences the category mappings. Forty L1-Korean learners of English listened to English nonsense words consisting of /p b t d f v θ ð/ and /ɑ/, with the consonants appearing in pre-stressed intervocalic, post-stressed intervocalic, or coda context, and were asked to identify the consonant with both Korean and English labeling and to give gradient evaluations of the goodness of each label to the stimuli. Results show that the mapping patterns differ extensively from those found previously with the same subjects for consonants in initial, onset context. The mapping patterns for the intervocalic context also differed by position with respect to stress location. Coda consonants elicited poor goodness-of-fit and noisier mapping patterns for all segments, suggesting that an L1 coda neutralization process put all L2-English sounds in codas as “new” sounds under the Speech Learning Model (SLM) framework (Flege, 1995). Taken together, the results indicate that consonant learning needs to be evaluated in terms of position-by-position variants, rather than just being a general property of the overall consonant systems.